Reaction time and anticipatory skill of athletes in open and closed skill-dominated sport - Nuri, L.; Shadmehr, A.; Ghotbi, N.; Attarbashi Moghadam, B. (European Journal of Sport Science, 2013)
In sports, reaction time and anticipatory skill are critical aspects of perceptual abilities. To date, no study has compared reaction time and anticipatory skill of athletes from open and closed skill-dominated sport. Accordingly, the present study investigated whether a difference exists in sensory-cognitive skills between these two different sport domains. Eleven volleyball players and 11 sprinters participated in this experiment. Reaction time and anticipatory skill of both groups were recorded by a custom-made software called SART (speed anticipation and reaction time test). This software consists of six sensory-cognitive tests that evaluate visual choice reaction time, visual complex choice reaction time, auditory choice reaction time, auditory complex choice reaction time, and anticipatory skill of the high speed and low speed of the ball. For each variable, an independent t-test was performed. Results suggested that sprinters were better in both auditory reaction times (P<0.001 for both tests) and volleyball players were better in both anticipatory skill tests (P = 0.007 and P = 0.04 for anticipatory skill of the high speed and low speed of the ball, respectively). However, no significant differences were found in both visual choice reaction time tests (P > 0.05 for both visual reaction time tests). It is concluded that athletes have greater sensory-cognitive skills related to their specific sport domain either open or closed.